2020
DOI: 10.3390/md18020105
|View full text |Cite
|
Sign up to set email alerts
|

Floridoside Exhibits Antioxidant Properties by Activating HO-1 Expression via p38/ERK MAPK Pathway

Abstract: Floridoside is a low-molecular-weight organic compound, which can be accumulated by red algae under stressful conditions to protect cells via its excellent antioxidant properties. In the present study, we investigated the antioxidant mechanism of floridoside toward human hepatocyte L-02 cells. We found that floridoside had no toxicity to L-02 cells, and no reactive oxidative species were induced by it either. However, the expression of hemoxygenase-1 (HO-1) protein was up-regulated upon exposure to floridoside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…To assess the interference effect of FUC on Nrf2-Keap1 binding, 266 nM Nrf2 and FUC of different concentrations were mixed, and the mixture was used to interact with Keap1 protein. The sensors were loaded with biotinylated Keap1 protein, and the immobilized sensor was dipped into the [18]. Briefly, treated cells were washed once with ice-cold PBS, followed by incubation with 10 μM carboxy-H2DCF-DA at 37°C for 10 min.…”
Section: Fortébio Octet System Assay For Binding Affinity Between Keamentioning
confidence: 99%
“…To assess the interference effect of FUC on Nrf2-Keap1 binding, 266 nM Nrf2 and FUC of different concentrations were mixed, and the mixture was used to interact with Keap1 protein. The sensors were loaded with biotinylated Keap1 protein, and the immobilized sensor was dipped into the [18]. Briefly, treated cells were washed once with ice-cold PBS, followed by incubation with 10 μM carboxy-H2DCF-DA at 37°C for 10 min.…”
Section: Fortébio Octet System Assay For Binding Affinity Between Keamentioning
confidence: 99%
“…These findings suggested that HO-1 induction by CoPPIX might contribute to HC protection against gentamicin-induced damage. Recent evidence also suggested that HO-1 was essential in modulating antioxidant effects in other tissues ( Shalaby et al, 2019 ; Niu et al, 2020 ). Park et al (2017) found that in the cochlear tissue, a peroxisome proliferator-activated receptor (PPAR) inducer protected HCs from gentamicin-induced toxicity by increasing the expression of HO-1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Nrf2 also regulate the key genes of heme metabolism ABCB6 , ABCG2 , HO-1 and heme responsive gene-1 to participate in the process of ferroptosis ( Hubner et al, 2009 ; Singh et al, 2010 ; Campbell et al, 2013 ; Dong et al, 2020 ). Among them, HO-1 is not only the key enzyme to decompose heme, but also an important antioxidant ( Tenhunen et al, 1968 ; Niu et al, 2020 ). Multiple studies have shown that activating the antioxidant response axis Nrf2/HO-1 is a crucial means of inhibiting ferroptosis and ameliorating myocardial ischemia-reperfusion injury, ulcerative colitis, and acute lung injury ( Chen et al, 2021b ; Li J. et al, 2021 ; Lv et al, 2021 ).…”
Section: The Regulatory Mechanism Of Ferroptosismentioning
confidence: 99%